Retrospective chart review of inherited and idiopathic dystonia - Alakkas, A.; Shinawi, H.; Bajwa, J. A.; Alsinaidi, O.; Al-Hashim, A. (Frontiers in Genetics, 2025)
Dystonia prevalence and presentation varies both ethnically and geographically. There is a paucity of data on the clinical presentation of dystonia patients in Saudi Arabia and among Arabs. In this study we provide the largest description of dystonia patients in Saudi Arabia. In our population, majority, 42% of all patients with dystonia had an inherited dystonia, while 34.8% had idiopathic dystonia. In addition, we found 3 patients with homozygous GCH1 variants who displayed the classic phenotype of dopa-responsive dystonia. Two had Variant of Uncertain Significance that has been recently reclassified as likely pathogenic, and another novel homozygous Asp119Asn variant, not previously reported in ClinVar. It is the hope that this paper would be the first step for future prospective studies.